Теорема Хилле - Иосида для резольвентных операторов многопараметрических полугрупп - Мишура, Ю.С.; Лаврентьев, А.С. (Український математичний журнал, 1996)
We consider multiparameter semigroups of two types (multiplicative and coordinatewise) and resolvent operators associated with such semigroups. We prove an alternative version of the Hille-Yosida theorem in terms of resolvent operators. For simplicity of presentation, we give statements and proofs for two-parameter semigroups.